The University of Zambia Department of Mathematics and Statistics MAT1110: Foundation Mathematics and Statistics For Social Sciences Tutorial Sheet 4

Download as pdf or txt
Download as pdf or txt
You are on page 1of 2

THE UNIVERSITY OF ZAMBIA

Department of Mathematics and Statistics


MAT1110: Foundation Mathematics and Statistics for Social Sciences
Tutorial Sheet 4
1. Find the partial-fraction decomposition of the following rational functions:

(a) i. ii. iii.


1 x+7 2x2 − 9x − 35
(x + 5)(x + 4) 2
x + 3x + 2 x3 + 2x2 − 5x − 6

(b) i. ii.
x2 + 2 4x
(x + 2)2 (x + 3) x3 + 4x2 + 5x + 2

(c) i. ii. iii.


x2 − 1 x−3 2x
x(x2 + 1) x3 + 3x (x + 1)2 (x2 + 1)

(d) i. ii. iii.


x2 + 1 4x3 + 10x + 4 2x4 + 3x2 + 1
x2 − 1 x(2x + 1) x2 + 3x + 2
2. (a) Solve each of the following quadratic inequalities, in each case, illustrating the solution set
on the number line.

i. iii.
2
2x + 3x ≥ 3 x2 + 2x ≤ 8
ii. iv.
x2 − 2x − 3 < 0 x2 − 3x − 4 6= 0

(b) Sketch each of the following quadratic functions. In each case, state the set of value(s) of x
for which f (x) > 0, f (x) ≤ 0.

i. iii.
2
f (x) = 2x + 3x − 3 f (x) = 2x2 − 4x + 5
ii. iv.
f (x) = −x2 − 4x + 1 f (x) = −2x2 − 3x + 2
(c) Solve each of the following cubic inequalities, in each case, illustrating the solution set on
the number line.

i. iii.
4x3 − x < 6 − 9x2 x3 − x2 − 9x + 9 ≤ 0
ii. iv.
(x + 4)(x − 2)(x − 7) > 0 4x3 − 8x2 − x + 2 6= 0

(d) Sketch each of the following cubic functions. In each case, state the set of value(s) of x for
which f (x) > 0, f (x) ≤ 0.

i. iii.
3 2
f (x) = 4x + 9x − x − 6 f (x) = x3 − 5x2 + 3x + 9
ii. iv.
f (x) = x3 − 5x2 − 22x + 56 f (x) = x4 + 4x3 − 12x2

3. (a) Solve each of the following rational inequalities, in each case, illustrating the solution set
on the number line.

i. v.
x−1 x x
≤0 ≤
x+2 x+1 x+2
ii.
x+2
≥1 vi.
x−1
iii. x−1
2 x(x − 1) >
x −9 x
<0
x2 − 1
vii.
iv.
x2 + 5x + 6 x−3 x+2
≤0 ≥
x2 − 4x − 5 x+4 x−5

(b) For each of the following rational functions, find/state the domain and the range. Hence
sketch the graph.

i. iii.
2−x x+1
f (x) = f (x) =
x+4 x−1
ii. iv.
3x + 6 2x + 5
f (x) = f (x) =
x−1 x−1

You might also like